2007
DOI: 10.1177/0954008307082508
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Properties of Polythioetherimides Derived from 4,4'-[p-Thiobis(phenylenesulfanyl)]Diphthalic Anhydride and Various Aromatic Diamines

Abstract: An asymmetrical aromatic diamine, 1-(4'-aminophenoxy)-4-(4'-aminophenylenesulfanyl) benzene (OSDA) was synthesized. A series of polythioetherimides (PTEIs) were prepared from a thioether-bridged aromatic dianhydride 4,4'-[ p-thiobis(phenylenesulfanyl)]diphthalic anhydride (3SDEA) and various aromatic diamines having ether or thioether linkages between phenylene rings by a two-step polycondensation procedure via their soluble poly(amic acid) (PAA) precursors. Medium to high molecular weight PAAs were obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is worthwhile to note that the T 5% of these copolyimides in air is higher than that in nitrogen which is just contrary to a majority of PIs. This phenomenon has been found in the other sulfur-containing polymers, which is ascribed to the different degradation mechanisms in various atmospheres [12,22].…”
Section: Basic Properties Of Homopolyimidesmentioning
confidence: 96%
See 1 more Smart Citation
“…It is worthwhile to note that the T 5% of these copolyimides in air is higher than that in nitrogen which is just contrary to a majority of PIs. This phenomenon has been found in the other sulfur-containing polymers, which is ascribed to the different degradation mechanisms in various atmospheres [12,22].…”
Section: Basic Properties Of Homopolyimidesmentioning
confidence: 96%
“…As a consequence, thioether links have been introduced to many polymers. And polythioetherimides have been synthesized by many researchers for different purposes [10][11][12]. In previous research, PIs based on 2,3,3',4'-thioetherdiphthalic anhydride (3,4'-TDPA) exhibited a higher T g than that of symmetric 3,3',4,4'-thioetherdiphthalic anhydride (4,4'-TDPA) and also presented a remarkable drop in the complex viscosity above T g [13].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was ascribed to the different degradation mechanisms in various atmospheres, which had been found in the other sulfur-containing polymers. 27,30,37 The first stage was the reaction process of sulfur and air and the second stage was the decomposition of the backbone of PIs.…”
Section: Resultsmentioning
confidence: 99%
“…The possible decomposition was that sulfur was oxidized to sulfoxide or sulfone in air. [39][40][41] All those T 5% values in air and under nitrogen atmospheres demonstrated that the isomeric PTIs possess moderate thermal and thermal oxidative stability. Furthermore, the thermal oxidative resistance of polymers can also be testified by the char yields, which were over 55% at 800 C under nitrogen atmosphere.…”
Section: Properties Of the Isomeric Ptismentioning
confidence: 95%